2020
DOI: 10.1042/bsr20200706
|View full text |Cite
|
Sign up to set email alerts
|

Association of rs662799 variant and APOA5 gene haplotypes with metabolic syndrome and its components: a meta-analysis in North Africa

Abstract: Apoliprotein protein A5 (APOA5) has been linked to metabolic syndrome (MetS) in several populations. In North Africa, only the Tunisian and Moroccan populations were investigated.  Our aim is to assess the association between APOA5 gene variant (rs662799) and haplotypes with MetS in Tunisian population and to perform a meta-analysis in North Africa. A total of 594 Tunisian participants were genotyped for polymorphism rs662799 using KASPar technology. Two polymorphisms rs3135506 and rs651821 in APOA5 gene genot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
2
10
0
Order By: Relevance
“…The power analysis demonstrated that our study sample size (299 controls/295 cases) does not affect the detection of significant association. Indeed, we have previously identified significant associations of APOA5 polymorphisms with the MetS in two studies performed on the same cohort of the present work [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…The power analysis demonstrated that our study sample size (299 controls/295 cases) does not affect the detection of significant association. Indeed, we have previously identified significant associations of APOA5 polymorphisms with the MetS in two studies performed on the same cohort of the present work [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 63%
“…This study is conducted in the frame of MEDIGENE project, that was approved by the Ethical committee of Institut Pasteur in Tunis (Reference IPT/LR11-05/Etude 04/2013) [ 25 ]. A total of 594 participants (299 controls and 295 MetS patients), aged between 35 and 75 years, were recruited and clinically characterized as previously described [ 26 , 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Our search strategy ( Figure 1 and Methods section) identified 36 studies that met our inclusion criteria ( Bayoumi et al, 2007 ; Bayoumy et al, 2012 ; Boumaiza et al, 2012a ; Boumaiza et al, 2012b ; Ghattas et al, 2013 ; Mohamed Youssef et al, 2013 ; Zadjali et al, 2013 ; Ajjemami et al, 2014 ; Al-Daghri et al, 2014 ; Mackawy and Badawi, 2014 ; Youssef et al, 2014 ; Ajjemami et al, 2015 ; Mehanna et al, 2015 ; Alnory et al, 2016 ; Mehanna et al, 2016 ; Elouej et al, 2016a ; RaafatAbdRaboh et al, 2016 ; Elouej et al, 2016b ; Elouej et al, 2016c ; Khella et al, 2017 ; Hasan et al, 2017 ; Lakbakbi El Yaagoubi et al, 2017 ; Mackawy, 2017 ; Morjane et al, 2017 ; Ismail et al, 2019 ; Ibrahim and Bastawy, 2020 ; Salami and El Shamieh, 2019 ; ElGhareeb et al, 2019 ; Nizam et al, 2019 ; Boulenouar et al, 2019 ; Aljaibeji et al, 2020 ; Osman et al, 2020 ; Alenad et al, 2020 ; Hechmi et al, 2020 ; Kefi, 2021 ). In most cases, studies were excluded because they lacked detailed results, such as odds ratios, confidence intervals, and p -values.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, this long-term study demonstrated that the minor C allele of the APOA5 gene (rs662799) is negatively related to the effect on triglycerides, insulin levels and HOMA-IR after consumption of a low-calorie diet with a Mediterranean pattern. Further studies are necessary to evaluate the importance of this SNV in the lipid profile and metabolic syndrome in different populations [39]. In the future, clinical guidelines will incorporate this knowledge to improve the design of nutritional interventions for obese patients, using panels of SNVs and other omic technologies [40].…”
Section: Discussionmentioning
confidence: 99%